Evaluasi Normatif Pembagian Sisa Hasil Usaha pada Koperasi Syariah: Perspektif Filsafat Hukum Utilitarianisme - Isniyati, Qodriyah; Wahyu Muhammad, Danang (Media of Law and Sharia, 2026)
This study aims to analyze the distribution of Net Surplus in Islamic cooperatives from a utilitarianism perspective, particularly in relation to achieving the greatest benefit for all members through the allocation of SHU. The establishment and operation of Islamic cooperatives in Indonesia are legally grounded in Law No. 25 of 1992 on Cooperatives and Minister of Cooperatives and SMEs Regulation No. 08 of 2023 on the Implementation of Savings, Loan, and Sharia Financing Activities by Cooperatives. Within the Islamic economic framework, cooperative activities are guided by the principle of maslahah (public welfare), which emphasizes the achievement of collective prosperity and the fulfillment of members’ fundamental needs. The distribution of Net Surplus is carried out proportionally based on members’ participation and business contributions within the cooperative. From a utilitarian perspective, this mechanism aims to maximize collective welfare by ensuring that the benefits generated from cooperative activities are distributed fairly among members. This study employs a juridical–philosophical method through the analysis of utilitarian legal philosophy and a conceptual approach to public interest. The novelty of this research lies in examining the rationale of Net Surplus distribution through utilitarian reasoning within the framework of Islamic cooperative principles. The findings indicate that Islamic cooperatives implement a form of rule utilitarianism by prioritizing members’ welfare in SHU distribution, while simultaneously upholding the principles of justice, legal certainty, and the protection of members’ rights.